Unresolved CFD and DEM Coupled Simulations on Scour around a Subsea Pipeline - Seongjin Song; Sunho Park (Journal of Marine Science and Engineering, 2022)
In this paper, numerical studies were carried out on scour around a subsea pipeline. A coupled solver between computational fluid dynamics (CFD) and discrete element method (DEM) was selected to simulate fluid flow and particle interactions. To select and validate the numerical model parameters in the solver, angles of repose and incipient motion were simulated. From the validation studies, the selected coefficient of rolling friction with spherical particles could predict the behavior of non-spherical particles. The fluid flow around the subsea pipeline was simulated, and the motion of individual soil particles was tracked. Particle motions were generated by the drag force, due to a high velocity. Three scour development process, such as onset of scour, tunnel erosion, and lee-wake erosion, were studied and discussed. The scour depth evolution showed good agreement with the experimental data. It was confirmed that the selected solver, with numerical model parameters, predicted the scour process around a subsea pipeline well.